On-The-Job Training: Enhance Experience and Increase Success for the Student Community in Vietnam - Tran Ba Loc; Nguyen Thi Thanh Ngan; Le Duy Linh; Nguyen Trong Luan (SAGE Open)
On-the-job training (OJT) programs at private universities play an essential role in providing students with real-world experiences, equipping them with the skills and knowledge needed for future career. Researching the factors that affect the effectiveness of OJT is extremely necessary to complete and improve the quality of this training program. The researchers conducted a quantitative study using nonprobability sampling to collect data from 335 people via the Google platform. After having data from respondents, the researcher coded the data in Microsoft Excel and analyze it in SPSS and Amos such as descriptive statistics, Cronbach’s Alpha, Exploratory Factor Analysis (EFA), structural equation modelling (SEM). The study found that OJT is affected by factors such as job characteristics, work environment, contextual factors, and university support. Besides, OJT affects various factors such as job satisfaction, career development, job involvement, and motivation to learn.